Quantitative indices for cone-beam CT assessment of Medication-Related Osteonecrosis of the Jaw - a scoping review - Ghaidaa Badabaan; Adriana G. Creanga; Steven R. Singer; Maxine Strickland; Gayathri Subramanian (Elsevier, 2023)
Objectives: It is not unusual for Medication-related osteonecrosis of the jaw (MRONJ) lesions that have similar clinical presentation and staging to have dissimilar radiographic extent of disease. The aim of this review was to explore the published scientific literature for quantitative indices that describe the cone-beam computerized tomography (CBCT) radiographic features of MRONJ lesions and assess their clinical utility. Method and Materials: A scoping review of the literature was performed to identify quantitative indices developed to describe the CBCT radiographic features of MRONJ lesions. Five electronic databases were included in the review: PubMed, Scopus, Web of Science, Trip medical database, and Cochrane Library. Articles published from the year 2003 onward were included in the review. Results: 367 articles were initially included in the review. 39 abstracts were screened for full-text assessment. The scoping review yielded 12 full length articles with169 cases reported. The Composite Radiographic Index score (CRI score) was identified as the most meaningful index in published literature that attempted to quantify qualitative radiographic changes (Walton, Grogan et al. 2019). However, lesions with similar CRI scores that corresponded to intermediate severity (3-5) may be very dissimilar radiographically in both nature and extent of radiographic changes, undercutting its clinical value. Conclusion: The CRI index score was the only relevant index for cross-sectional (one-time) assessment of established MRONJ lesions (non-stage 0). This scoping review yielded several critical questions regarding the clinical significance and prognostic implications of various radiographic changes in MRONJ, thereby identifying focus areas for future research.